Analisis Pemahaman Mahasiswa PGSD Terhadap Nilai Karakter Bangsa Dalam Mata Kuliah Pendidikan Karakter - Dea Mustika; Febrina Dafit (Universitas Negeri Padang, 2019)
This research aims to investigate the students' understanding of the values of national character in the subject of character education in elementary school. This research used a descriptive quantitative approach. This research was conducted at the PGSD study program, FKIP, Riau Islamic University. The population of this research included 128 sstudents of class 2017. 56 students were taken as research samples using proportional simple random techniques for an error rate of 10%. The method of data analysis uses descriptive analysis by describing the opinions of respondents based on the answers of the questionnaire instruments tested. The results of the study indicate that PGSD students' understanding of national character values is good. This is indicated by the overall end result for eighteen national character values is 82% in the good category.